WhiB4 Is Required for the Reactivation of Persistent Infection of Mycobacterium marinum in Zebrafish - Chen Lin (Microbiology Spectrum, 2022)
ABSTRACT Granulomas are the pathological hallmark of tuberculosis (TB). In individuals with latent TB infection, Mycobacterium tuberculosis cells reside within granulomas in a nonreplicating dormant state, and a portion of them will develop active TB. Little is known on the bacterial mechanisms/factors involved in this process. In this study, we found that WhiB4, an oxygen sensor and a transcription factor, plays a critical role in disease progression and reactivation of Mycobacterium marinum (M. marinum) infection in zebrafish. We show that the whiB4::Tn mutant of M. marinum caused persistent infection in adult zebrafish, which is characterized by the lower but stable bacterial loads, constant number of nonnecrotized granulomas in fewer organs, and reduced inflammation compared to those of zebrafish infected with the wild-type bacteria or the complemented strain. The mutant bacteria in zebrafish were also less responsive to antibiotic treatments. Moreover, the whiB4::Tn mutant was defective in resuscitation from hypoxia-induced dormancy and the DosR regulon was dysregulated in the mutant. Taken together, our results suggest that WhiB4 is a major driver of reactivation from persistent infection. IMPORTANCE About one-quarter of the world’s population has latent TB infection, and 5 to 10% of those individuals will fall ill with TB. Our finding suggests that WhiB4 is an attractive target for the development of novel therapeutics, which may help to prevent the reactivation of latent infection, thereby reducing the incidences of active TB.